2023
DOI: 10.1101/2023.08.31.555794
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neuronal acid-sensing ion channel 1a regulates neuron-to-glioma synapses

Gyeongah Park,
Zhen Jin,
Qian Ge
et al.

Abstract: Neuronal activity promotes high-grade glioma progression via secreted proteins and neuron-to-glioma synapses, and glioma cells boost neuronal activity to further reinforce the malignant cycle. Whereas strong evidence supports that the activity of neuron-to-glioma synapses accelerates tumor progression, the molecular mechanisms that modulate the formation and function of neuron-to-glioma synapses remain largely unknown. Our recent findings suggest that a proton (H+) signaling pathway actively mediates neuron-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 74 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…Interestingly, a recent study, which has not yet been peerreviewed, reported reduced tumour growth and prolonged survival of mice after transplanting the murine glioma cell line GL261 into the brain of mice with ASIC1a gene deletion [59]. Importantly, ASIC had been knocked-out in the host tissue and not in the tumour cells.…”
Section: Asics In Brain Cancer -Increased Migration Vs Increased Cell...mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a recent study, which has not yet been peerreviewed, reported reduced tumour growth and prolonged survival of mice after transplanting the murine glioma cell line GL261 into the brain of mice with ASIC1a gene deletion [59]. Importantly, ASIC had been knocked-out in the host tissue and not in the tumour cells.…”
Section: Asics In Brain Cancer -Increased Migration Vs Increased Cell...mentioning
confidence: 99%
“…ASIC expression in GL261 cells was not assessed. The authors proposed that the acidic TME increased ASIC signalling also in neighbouring neurons leading to an increased connectivity between neurons and glioma [59], which is known to drive glioma progression [77][78][79]. However, the mechanisms and signalling pathways underlying this regulatory role of ASIC1a on neuron-glioma connectivity remained unclear.…”
Section: Asics In Brain Cancer -Increased Migration Vs Increased Cell...mentioning
confidence: 99%